KARAKTERISASI MORFOLOGI DAUN DAN BUNGA BEBERAPA VARIETAS Hoya coronaria DARI KAWASAN HUTAN KERANGAS AIR ANYIR, BANGKA - Putri Deswanti; Yulian Fakhrurrozi; Sri Rahayu (EKOTONIA: Jurnal Penelitian Biologi, Botani, Zoologi, dan Mikrobiologi, 2017)
Hoya coronaria was found in Heath Forest Air Anyir, Bangka in various flower color. Characterization based on morphological characteristics need to clear up the differences between varieties. This research aims to observe morphological variation of six varieties of H. coronaria from Heath Forest Air Anyir, Bangka based on morphology vegetative and flower morphology. The descriptive method was used to describe the morphological character. Determination of color based on Munsell Color Chart for Plant Tissues. The six samples of different varieties was used which has different flower color as follow respectively: yellow corolla with pink corona (var1); yellow corolla with white corona (var2); yellow corolla with pink honey line and pink corona (var3); pink corolla with pink honey line and pink corona (var4); pink corolla with pink honey line and white corona (var5); and white corolla with white corona (var6). The six varieties have different characteristic of vegetative and flower part both on qualitative and quantitative measurement. The cluster analyses resulted two sister groups. The first group (group A) consisted of var3, var4, var5, and var6, and the second group (group B) consisted of var1 and var2. Groups A was consisted of two smaller groups, namely group C and group D. Group C consisted of var3, var4 and var5, while group D consisted of var6